Scope and relevance of customary arbitration as mechanism for settlement of dispute in the 21st century (2019)
This paper examines the scope and relevance of customary arbitration proceedings in Nigeria prior to the advent of modern arbitration practice. The paper argues for the relevance of customary arbitration in this 21st century. It discusses the basic characteristics and requirements of a valid customary arbitration. The paper submits that the validity of customary arbitral award is determined by voluntary submission of dispute by parties to traditional arbitrator(s) recognised under native law and custom and that in the absence of any vitiating elements that may affect the voluntariness or otherwise of such an arbitral process, the arbitration is binding on the parties and would operate as estoppel to bar subsequent proceedings between the parties. The paper advocates for the adoption of customary arbitration as dispute settlement mechanism in Nigeria along-side the statutory arbitration to give parties the option of choosing either of the two mechanisms for resolution of their disputes.